The The Legitimacy of CJEU in the Settlement of Trade Mark Disputes between Non-European Union Foreign Companies: A Case Study - Musthafa, Annas Rasid; Putrazta, Satriya Aldi; Efendi, A’an (Faculty of Law Universitas Lampung, 2023)
Protection of Intellectual Property Rights (IPR) is important for companies to maintain brand awareness. One of the challenges in trademark protection involves resolving disputes under a supranational organization, specifically The Court of Justice of the European Union (CJEU). This Court has jurisdiction to adjudicate cases involving foreign companies from non-EU countries, which can present complexities for those entities navigating the legal framework and protections afforded within the EU. This research examined the authority, legitimacy, and application of justice through CJEU in resolving disputes between foreign companies. This normative legal research used a statute approach, case study, and library research. Based on the research results, the authority and legitimacy of CJEU in resolving disputes with foreign companies have been regulated in the Maastricht treaty. The submission of foreign companies is also related to the opposing party, a company flagged by an EU member state. The use of CJEU in resolving disputes requires parties to maximize all judicial remedies available at the national before proceeding to the international level.